The Correlation Between Academic Achievement and Gratitude Students in SMK GM Jombang - Marhamah, Lintang (Asosiasi Psikologi Islam (API) Himpsi, 2022)
This study aims to determine the relationship between gratitude and academic achievement of students at SMK GM Jombang. The research method used in this study is correlational quantitative research with data collection using the gratitude instrument developed by Listiyandini et al., (2015) in the form of a Likert scale and the average student grade point in one semester. The subjects in this study were all students who were undergoing a period of study at SMK GM Jombang in the 2020/2021 academic year. The hypothesis was tested in this research using Pearson's product moment method with the help of SPSS for windows ver25. The findings in this study concluded that gratitude has a positive relationship on student academic achievement with a significance of 0.00<0.05.